Pemberdayaan Masyarakat Desa melalui Literasi Akuntansi Digital pada Program Catat Uang Desa dengan Cerdas - Daud, Maiercherinra; Sanda Sip, Afian Dezi; Sambo, Eva Marin; Suriyadi Nur; Ana Rusmardiana (ADPERTISI, 2025)
This community service program aims to improve the literacy and digital accounting skills of residents of Kalukuang Village, Takalar Regency, through the